ANALISIS PERKEMBANGAN BAHASA ANAK SINDROM DOWN - Ashari, Novita; Azis, Andi Sri Ramadana; Nadia, Nadia (JIVA: Journal of Behaviour and Mental Health, 2024)
ABSTRACTDown syndrome children have problems in language development because they have communication difficulties. The purpose of this study is to analyze language development in children with Down syndrome. The method used by researchers in qualitative research with a case study approach. Data collection techniques used are interview techniques, documentation, and observation. This research was conducted in class 2 SLB Negeri 1 Parepare City. The subjects in this study had the initials AN and SY. AN is 13 years old while SY is 9 years old. The results showed that AN had not been able to learn about the contextual meaning of punctuation marks, had not been able to use polite language and had not been able to compare language styles. While SY is not yet able to speak, is not brave enough to appear in public with effective grammar skills, is not interested in visual media and is not yet able to have adult-like speech patterns.Keyword:  Language Development, Down Syndrome ABSTRAKAnak sindrom down mempunyai permasalahan dalam perkembangan bahasa karena memiliki kesulitan pada komunikasi. Tujuan dari penelitian ini yaitu untuk menganalisis perkembangan bahasa pada anak sindrom down. Metode yang digunakan oleh peneliti dalam penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalah Teknik wawancara, dokumentasi, dan observasi. Penelitian ini dilakukan di kelas 2 SLB Negeri 1 Parepare. Subjek dalam penelitian ini berinisial AN dan SY. AN 13 tahun sementara SY berusia 9 tahun. Hasil penelitian menujukkan bahwa AN belum mampu belajar mengenai makna konteks tanda baca, belum mampu menggunakan bahasa yang sopan dan belum mampu membandingkan gaya bahasa. Sementara SY belum mampu dalam berbicara, belum cukup berani tampil di depan umum dengan mampu memiliki pola bicara yang seperti orang dewasa.Kata kunci: Perkembangan Bahasa, Sindrom Down